PEtROGRAPHIC AND GEOCHEMICAL STUOIES OF SOME PHOSPHORITE '- DEPOSITS OF HAZARA, PAKISTAN (Biological Sciences - PJSIR, 2022)
Samples from Kakul mine and trenches of several phosphorite deposits were studied. These phosphorites oecurin gradational contact with siltstone, dolomite and chert belonging to Abbottabad Cambrian System. Thinly beddedphosphorites occur mostly as pellets and microsphoritc, while the intraclasts and pseudo-oolites are rare. Fluorapatiteis abundant in all the samples, while quartz, calcite, dolomite, feldspar, illite and hematite occur in minor phases. Thesephosphorites are primary marine sediments formed mostly by direct precipitation. Recrystallization is due to intense diagenesis,whereas fcrruginization suggests weathering of phosphatic horizons in Hazara.